2011
DOI: 10.1016/j.yjmcc.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a therapeutic target in cardiovascular disease

Abstract: The epidemic of heart failure continues apace, and development of novel therapies with clinical efficacy has lagged. Now, important insights into the molecular circuitry of cardiovascular autophagy have raised the prospect that this cellular pathway of protein quality control may be a target of clinical relevance. Whereas basal levels of autophagy are required for cell survival, excessive levels – or perhaps distinct forms of autophagic flux – contribute to disease pathogenesis. Our challenge will be to distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 122 publications
3
121
0
1
Order By: Relevance
“…22,23 It has been shown that basal levels of autophagy are essential for cardiac homeostasis under physiological conditions. Atg (autophagyrelated gene) 5 deficiency results in loss of amino acids and ATP availability in the heart, thus leading to neonatal death.…”
mentioning
confidence: 99%
“…22,23 It has been shown that basal levels of autophagy are essential for cardiac homeostasis under physiological conditions. Atg (autophagyrelated gene) 5 deficiency results in loss of amino acids and ATP availability in the heart, thus leading to neonatal death.…”
mentioning
confidence: 99%
“…Several autophagy-related (Atg) proteins are involved in forming, expanding and elongating the isolation membrane. (For in-depth discussions of these Atg proteins, see Nemchenko et al, 2011;Mizushima et al, 2011;Wesselborg and Stork, 2015;Nishida et al, 2015.) The membrane becomes enclosed around its cargo to create a doublemembraned autophagosome (Nishida et al, 2015;Nemchenko et al, 2011;Eskelinen et al, 2005).…”
Section: Autophagymentioning
confidence: 99%
“…(For in-depth discussions of these Atg proteins, see Nemchenko et al, 2011;Mizushima et al, 2011;Wesselborg and Stork, 2015;Nishida et al, 2015.) The membrane becomes enclosed around its cargo to create a doublemembraned autophagosome (Nishida et al, 2015;Nemchenko et al, 2011;Eskelinen et al, 2005). Material degraded through macroautophagy includes defective mitochondria, ribosomes, peroxisomes, endoplasmic reticulum and additional membrane structures, glycogen, lipid granules and other cytosolic aggregates (Kovsan et al, 2010;Kundu et al, 2008;Kuma and Mizushima, 2010;Schneider and Cuervo, 2014;Shires and Gustafsson, 2015;Nishida et al, 2015).…”
Section: Autophagymentioning
confidence: 99%
“…The above results also stress the significance of the severity and duration of the ischaemic event, to allow a sufficient induction of the autophagic machinery to take place. In fact, a direct relationship between autophagic flux and myocardial function has recently been proposed [50], indicating the strong need to measure autophagic activity accurately. Further characterization of the autophagic flux in clear context with myocardial injury will help to answer questions when autophagy functions as a primarily destructive pathway, manifesting in type II programmed cell death or when autophagy functions in a cytoprotective manner.…”
Section: Autophagy and Myocardial Metabolismmentioning
confidence: 99%